The Effect of Asset Structure and Business Risk on Capital Structure with Profitability as the Moderating Variable - Buana, Fita Kartika; khafid, muhammad (Accounting Analysis Journal, 2018)
The aims of this research to analyze the effect of asset structure and business risk to capital structure with profitability as moderating variable. The population of this study is property and real estate companies listed on the Indonesia Stock Exchange (BEI) during the year 2013-2016. The population are 48 companies and 24 research samples. Data were selected by purposive sampling technique which obtained by 96 unit of analysis. This research uses secondary data taken from annual financial statements. Data collection technique used is documentation techniques by collecting the required data from the annual financial reports. Moderated regression analysis data by difference absolute value test was used to analyse data. The result of this research revealed that asset structure significant positive effect on capital structure. Meanwhile, business risk negatively effect on capital structure. In addition, the profitability can weaken the effect of assets structure on capital structure. However, the profitability not moderating the effect of business risk on capital structure. Based on the result of research, it can be concluded that capital structure is influenced by asset structure and business risk and profitability can moderate the effect of asset structure on capital structure.